2013
DOI: 10.1007/s10840-013-9850-2
|View full text |Cite
|
Sign up to set email alerts
|

Findings on magnetic resonance imaging of fascicular ventricular tachycardia

Abstract: Detection of local areas of fibrosis or scar by DE-MRI may help to distinguish idiopathic fascicular tachycardia from scar-related fascicular VT in patients with preserved left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The essence of the slow conduction zone is unknown but may be some ventricular myocardium or abnormal Purkinje fiber with decremental conduction properties. Herkommer et al 7 reported local areas of fibrosis or scar corresponded to the successful ablation sites of LPF-VT in 3 of 9 patients seen via magnetic resonance imaging. In certain LPF-VT cases, myocardial scar may represent an alternative reason for the presence of a slow conduction zone.…”
Section: Property Of P1 and Slow Conduction Zonementioning
confidence: 99%
“…The essence of the slow conduction zone is unknown but may be some ventricular myocardium or abnormal Purkinje fiber with decremental conduction properties. Herkommer et al 7 reported local areas of fibrosis or scar corresponded to the successful ablation sites of LPF-VT in 3 of 9 patients seen via magnetic resonance imaging. In certain LPF-VT cases, myocardial scar may represent an alternative reason for the presence of a slow conduction zone.…”
Section: Property Of P1 and Slow Conduction Zonementioning
confidence: 99%
“…Although classically regarded as a ‘normal heart arrhythmia’, recent studies have demonstrated focal myocardial abnormalities on imaging and association with SHD and myocardial ischaemia 38. The VT may be incessant and can be difficult to suppress with medications.…”
Section: Non-inherited Vt In Structurally Normal Heartsmentioning
confidence: 99%
“…Cardiac MRI was performed in our institution in 47 patients and in other institutions in 11 patients. In most patients, DE‐MRI was performed before ablation.…”
Section: Methodsmentioning
confidence: 99%